PENGETAHUAN RASIONAL MURNI: Antara Teorema Penciptaan dan Teori Evolusi - Gunawan, Leo Agung Srie; Vivaldi, Gerardo; Ara, Alfonsus (UNIKA Santo Thomas, 2023)
This article means to explain the epistemology of Immanuel Kant. According to Kant, epistemology has to start from the knowing subject than the known object. Here, it happens the reversal of epistemology as the Copernican revolution. The main reason is that what is known by man contends in the object which appears to the subject (phänomenon) and is not the object itself (noumenon). Based on this, Kant applies the epistemological principle “synthetic a priori,” which elaborated on the thought of transcendental esthetic, transcendental logic, and transcendental dialectic. The transcendental esthetic represents the object precepted by the senses, and then the transcendental logic processes it with the categories in the reason. Particularly, Kant asserts that the soul, the world, and God in the transcendental dialectic are the ideas of intellect, but they do not have natural objects. Finally, he clarifies how the paradigm of transcendental idealism becomes the reconciliation between Rationalism and Empiricism in the way of epistemology